Profile of photic driving in electroencephalography records at Mohammad Hoesin Hospital Palembang - Sri Handayani; Erial Bahar; Olivia Amanda (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Photic driving (PD) is a normal electroencephalography phenomenon in the parietooccipital region during intermittent photic stimulation (IPS). The PD response is an indicator that is sensitive to age, brain maturity, certain abnormalities, changes in brain signal and brain complexity. Currently, there is not much data about the PD response based on individual characteristics. Methods: It is a cross-sectional study with secondary data from EEG and medical records, from January to December 2017. Result: Of 536 records, only 444 EEG records fulfilled the research criteria. PD response was more common in women (61.4%) and age group between 20-60 years (78.6%). Normal EEG result was 71.4%. PD responses were most commonly diagnosed with epilepsy etiology (33.8%). Only 28.6% of PD responses were found in abnormal EEG results. Conclusion: Distribution showed that the response of PD decreased in older age. The PD response is more common in patients with normal EEG results. The more abnormal results of EEG, PD response rarely arise.